(untitled) (Research, Society and Development, 2020)
The present study aimed to evaluate the impact of different chemical surface treatments and aging on dentin bond strength and nanoleakage of semi-direct restorations cemented with self-adhesive resin cement. One hundred and sixty semi-direct composite restorations (4.8 x 2.8 x 4.0 mm) were produced to fill dentin preparations in bovine tooth, and the specimens were divided into 8 groups according to chemical treatment [No treatment, Silane (S), Scotchbond™ Universal adhesive (SBU), and S+SBU], and aging time in water [24 h and 6 months]. Push-out bond strength (PBS) was measured through a universal testing machine (1.0 mm/min), failure modes by a dissecting microscope, and nanoleakage by scanning electron microscopy. Two-way ANOVA and Tukey’s post-hoc (p<0.05) test were used to analyze PBS data, whilst failure modes and nanoleakage were analyzed descriptively. The bond durability was influenced by different chemical surface treatments after 6 months of aging in distilled water, with the best performance for the group that uses silane associated with the universal adhesive. Nanoleakage was greater at the dentin-cement interface, from the base of the restorations. However, the infiltration of silver crystals at the cement-resin interface was not influenced by the different chemical treatments applied. The results of the study suggest that self-adhesive cement promotes efficient adhesion to the interface that improves over time without the need for chemical surface treatment or when using SBU, with or without silane.